Analisis Puisi “Sajak Atas Nama” Karya Mustofa Bisri Dengan Pendekatan Struktural (International Forum of Researchers and Lecturers, 2023)
Poetry is one of the literary works that has beauty in its composition. It is equipped with beautiful diction, a tone full of feelings such as disappointment, emotion, or even full of love. This research is motivated by the author's curiosity about the implied meaning of poetry. The purpose of this analysis is to find out in detail the meaning of each inner and physical structure. The method used in this study is a qualitative descriptive method with a structural approach. The results of this study found the entire physical structure and inner structure in the poem